Kinetics of oxidation of sulfur compounds: Rapid oxidation in new design of oscillatory baffled reactor - T. Nawaf, ِِAmer; Abdul Majeed, Basma A.; Haldhar, Rajesh (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
Recently, one of the most crucial objectives for the petroleum refining industries is producing clean or eco-friendly fuel. The world demands clean diesel utilizing simple processes under safe conditions (i.e., moderate operating conditions). For this purpose, an oscillatory helical baffled reactor (OHBR) was designed to improve the oxidative desulfurization (ODS) process, which is achieved here by converting sulfur compounds found in diesel fuel using a new homemade nanocatalyst. First, the homemade catalyst support, γ-alumina nanoparticles, was prepared using precipitation technology. The γ-Al2O3 was then used to design the synthetic nanocatalyst made of iron oxide using the IWI technology with 5% Fe2O3. A good distribution of the metal oxides has maintained a good surface area (SA) and pore volume (PV), resulting in high activity. The ODS of sulfur compounds and the performance of the modified nano-catalyst at different safe reaction conditions (frequency of oscillation from 0-2 Hz, amplitude of oscillation from 2-8 mm, reaction temperature from 50-80 oC and residence time only 9 min) were evaluated in the new designed OHBR. The best removal of sulfur was 73.23% at an oscillation frequency of 2 Hz, oscillation amplitude of 8 mm, and oxidation reaction of 80 oC with a residence time of 9 min under constant pressure. A kinetic model related to the sulfur oxidation from real diesel fuel by the ODS process in the OHBR was also investigated in this manuscript to estimate the best kinetic parameters of the relevant reactions in the first order.